Business process management : Blockchain and Central and Eastern Europe Forum : BPM 2019 Blockchain and CEE Forum, Vienna, Austria, September 1-6, 2019, proceedings /: Blockchain and Central and Eastern Europe Forum : BPM 2019 Blockchain and CEE Forum, Vienna, Austria, September 1-6, 2019, proceedings. ([2019]) - Unknown
No abstract available